Використання експертних оцінок при визначенні споживчих властивостей трактора ХТЗ-17021 - Смоловик, Раїса Федорівна; Чекаліна, Елеонора Петрівна; Сікєтіна, Наталія Геннадіївна; Шутько, Людмила Борисівна (НТУ "ХПИ", 2005)
Для визначення рівню конкурентоспроможності певної продукції використано метод рангової кореляції. За значущістю обрано технічні параметри. Виявлено найважливіші якісні властивості на думку споживачей за допомогою методу експертних оцінок.

By intensifying of competition native enterprises is facing a problem of guaranteeing of manufacturing production’s competitiveness. But, before make a decisions concerning to actions for maintenance of production’s competitiveness level, it is essential to determine level of competitiveness of manufacturing production on the market in comparison with production of enterprises-competitors.
Keywords: конкуренція; продукція; ринок; рангова кореляція; матриця; критерій згоди; ранг